Analytical performance of the FIPPS/IFIN facility at ILL - Révay Zsolt; Jentschel Michael; Michelagnoli Caterina; Colombi Giacomo; Domenichetti Lorenzo (EPJ Web of Conferences, 2025)
The FIPPS/IFIN facility at ILL has been applied successfully for nuclear physics measurements. Its 16 Clover detectors enable unique high-efficiency gamma-gamma coincidence measurements for the investigation of level schemes of neutron activated targets. This instrument could be used for nuclear analytical purposes, too, because it detects the capture gamma rays as it is carried out in prompt gamma activation analysis. The Grenoble instrument is not optimized for analytical applications; however, its special characteristics offer a unique opportunity for the detection of hard-to-measure nuclides. This paper summarizes the results of the first experiments to investigate the analytical capabilities of the high-efficiency coincidence counting.